Epitopes in the capsular polysaccharide and the porin OmpK36 receptors are required for bacteriophage infection of Klebsiella pneumoniae - Rhys A. Dunstan; Rebecca S. Bamert; Kher Shing Tan; Uvini Imbulgoda; Christopher K. Barlow; George Taiaroa; Derek J. Pickard; Ralf B. Schittenhelm; Gordon Dougan; Francesca L. Short; Trevor Lithgow (Cell Reports, 2023)
Summary: To kill bacteria, bacteriophages (phages) must first bind to a receptor, triggering the release of the phage DNA into the bacterial cell. Many bacteria secrete polysaccharides that had been thought to shield bacterial cells from phage attack. We use a comprehensive genetic screen to distinguish that the capsule is not a shield but is instead a primary receptor enabling phage predation. Screening of a transposon library to select phage-resistant Klebsiella shows that the first receptor-binding event docks to saccharide epitopes in the capsule. We discover a second step of receptor binding, dictated by specific epitopes in an outer membrane protein. This additional and necessary event precedes phage DNA release to establish a productive infection. That such discrete epitopes dictate two essential binding events for phages has profound implications for understanding the evolution of phage resistance and what dictates host range, two issues critically important to translating knowledge of phage biology into phage therapies.